Sarcoidal Granulomatous Panniculitis Associated with Immune Checkpoint Inhibitors: A Rare Immune-Mediated Cutaneous Adverse Event - Di Prinzio, Anamá; Riganti, Julia; Torre, Ana C.; Mazzuoccolo, Luis D. (Revista del Hospital Italiano de Buenos Aires, 2025)
Immune checkpoint inhibitors (ICIs), or checkpoint inhibitors, have been associated with various inflammatory and autoimmune adverse effects, known as immune-related adverse events (irAEs). Among irAEs, dermatological toxicities are the most prevalent, with maculopapular rash, pruritus, and lichenoid and psoriasiform eruptions being the most common.
Keywords: Sarcoidosis; cancer; immunotherapy; immune checkpoint